1975
DOI: 10.1029/jb080i005p00742
|View full text |Cite
|
Sign up to set email alerts
|

Numerical models of convection in the upper mantle

Abstract: Two‐dimensional numerical models of steady state convection show that convection cells of aspect ratio as large as 8.6 are possible for variable viscosity convection in the upper mantle. Our models include the effects of variable viscosity, viscous dissipation, internal heating, heat flow through the bottom, and the adiabatic gradient. The large aspect ratio of the convection cells is primarily due to the large viscosity contrast between the lithosphere and the asthenosphere. It appears possible for multiple c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Thus Parmentier, Turcotte & Torrance (1976) found that a stressdependent rheology had very little effect on the flow pattern, while flow patterns with depth or temperature dependent viscosity calculated by Torrance & Turcotte (1971) and Houston & De Bremaecker (1975) were significantly affected, but also had internal variations of viscosity of two or more orders of magnitude. It is notable that Houston & De Bremaecker (1975) calculated cells with large aspect ratios (width to depth) in situations with high viscosities near the upper boundary, which was free to niove. Coinparisoil with calculations with imposed moving upper boundaries (Richter 1973;Parmentier 1976).…”
Section: Discussionmentioning
confidence: 94%
“…Thus Parmentier, Turcotte & Torrance (1976) found that a stressdependent rheology had very little effect on the flow pattern, while flow patterns with depth or temperature dependent viscosity calculated by Torrance & Turcotte (1971) and Houston & De Bremaecker (1975) were significantly affected, but also had internal variations of viscosity of two or more orders of magnitude. It is notable that Houston & De Bremaecker (1975) calculated cells with large aspect ratios (width to depth) in situations with high viscosities near the upper boundary, which was free to niove. Coinparisoil with calculations with imposed moving upper boundaries (Richter 1973;Parmentier 1976).…”
Section: Discussionmentioning
confidence: 94%
“…The widely used iterative techniques (e.g. Richter 1973;McKenzie :1977;Lux, Davies & Thomas 1979;Davies 1986) start with an estimate for ox (or SZx) on the boundaries and then solve the second-order equations separately, using Dirichlet boundary conditions on each. From this interim solution an improved estimate for w, (or SZ,) on the boundaries is then obtained by enforcing the zero-gradient condition on V x (or Yx).…”
Section: Solution Algorithm 11: Rigid Boundariesmentioning
confidence: 99%
“…An important addition regarding 2‐D mantle convection calculations is the inclusion of temperature dependent viscosity. The calculations done by Houston & De Bremaecker (1975), Parmentier et al (1976), Daly (1980), Jacoby & Schmeling (1982), Tackley (1993), Christensen (1984), Moresi & Solomatov (1995) and Ratcliff et al (1997) all included temperature dependent viscosity. Moresi & Solomatov (1995) reveal three different convection regimes in fluids with variations in viscosity.…”
Section: Introductionmentioning
confidence: 99%